Solid-state chemical recycling of polycarbonates to epoxides and carbon dioxide using a heterodinuclear Mg(II)Co(II) catalyst - Williams, C; Deacy, A; Buchard, A; McGuire, T (American Chemical Society, 2022)
Polymer chemical recycling to monomers (CRM) could help improve polymer sustainability, but its implementation requires much better understanding of depolymerization catalysis, ensuring high rates and selectivity. Here, a heterodinuclear [Mg(II)Co(II)] catalyst is applied for CRM of aliphatic polycarbonates, including poly(cyclohexene carbonate) (PCHC), to epoxides and carbon dioxide using solid-state conditions, in contrast with many other CRM strategies that rely on high dilution. The depolymerizations are performed in the solid state giving very high activity and selectivity (PCHC, TOF = 25700 h–1, CHO selectivity >99 %, 0.02 mol %, 140 °C). Reactions may also be performed in air without impacting on the rate or selectivity of epoxide formation. The depolymerization can be performed on a 2 g scale to isolate the epoxides in up to 95 % yield with >99 % selectivity. In addition, the catalyst can be re-used four times without compromising its productivity or selectivity.